2008
DOI: 10.1242/jeb.013714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary polyunsaturated fatty acids on mitochondrial metabolism in mammalian hibernation

Abstract: SUMMARYThirteen-lined ground squirrels (Spermophilus tridecemlineatus) were fed one of four isocaloric, isolipemic diets containing 16, 22, 35 or 55 mg linoleic acid (18:2n-6) per gram. Mitochondrial properties were compared between hibernating and summer active states, and between diet groups. As in other studies, state 3 respiration was significantly reduced in hibernation, but only in animals fed the 22 mg g -1 18:2 diet. In the other diet groups, there was no difference in state 3 respiration between the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 58 publications
7
33
0
Order By: Relevance
“…With saturating (10mmoll -1 ) succinate levels, the extent of suppression (52 and 33% in liver and skeletal muscle, respectively, compared with IBE) was comparable to previous studies (Gehnrich and Aprille, 1988;Muleme et al, 2006;Gerson et al, 2008;Armstrong and Staples, 2010;Chung et al, 2011;Brown et al, 2012), but the extent of suppression tended to decline with succinate concentration. For example, with 1mmoll -1 succinate, the extent of suppression was 42% in liver and 12.5% in skeletal muscle.…”
Section: Respiration Rate Is Lower In Mitochondria From Torpid Animalsupporting
confidence: 86%
See 1 more Smart Citation
“…With saturating (10mmoll -1 ) succinate levels, the extent of suppression (52 and 33% in liver and skeletal muscle, respectively, compared with IBE) was comparable to previous studies (Gehnrich and Aprille, 1988;Muleme et al, 2006;Gerson et al, 2008;Armstrong and Staples, 2010;Chung et al, 2011;Brown et al, 2012), but the extent of suppression tended to decline with succinate concentration. For example, with 1mmoll -1 succinate, the extent of suppression was 42% in liver and 12.5% in skeletal muscle.…”
Section: Respiration Rate Is Lower In Mitochondria From Torpid Animalsupporting
confidence: 86%
“…We chose to examine succinate-fuelled metabolism in the present study because (i) it is the most common substrate used in studies of mitochondrial metabolism in hibernating animals, and (ii) it allowed us to examine changes to an important segment of the electron transport chain without confounding effects from upstream processes that may be differentially regulated, for example, to shift fuel use away from carbohydrates rather than to suppress metabolism per se (Buck et al, 2002). For the most part, the results confirmed observations in previous studies made using saturating succinate concentrations (Gehnrich and Aprille, 1988;Muleme et al, 2006;Gerson et al, 2008;Armstrong and Staples, 2010;Chung et al, 2011;Brown et al, 2012), but two important facts were revealed by the present study. First, the degree of mitochondrial metabolic suppression during torpor is lower at sub-saturating compared with saturating succinate levels because torpid mitochondria are less sensitive to changes in succinate concentration than IBE mitochondria.…”
Section: Perspectives and Significancesupporting
confidence: 77%
“…Regulation of respiration rates, coupling and phosphorylation efficiency during short-term hypoxia are presumably controlled by several adjustments of the respiratory chain. Reduction of state 3 could result from inhibition of the phosphorylation system (reactions that generate or utilize ATP), the substrate oxidation system (reactions responsible for generating proton motive force) or both (Gerson et al, 2008). The increase of CCO activity during hypoxia in oysters (reported per nmol of cytochrome a) is unlikely a candidate for respiratory inhibition but suggests an involvement of this complex in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Diet and in vitro manipulations have been used to alter the fatty acid composition of phospholipids. The resulting changes in membrane fluidity, permeability, n-3/n-6 ratio, and local molecular environment play important roles in modulating the activities of key membrane proteins (Gerson et al, 2008;Guderley et al, 2008;Murphy, 1990;Stillwell et al, 1997). They include enzymes from oxidative pathways, ATPases, hormone receptors and ion channels [carnitine palmitoyl transferase (CPT) (Guo et al, 2005;Power and Newsholme, 1997); citrate synthase (CS) (Miyasaka et al, 1996); Na + /K + -ATPase; insulin receptor (Corcoran et al, 2007); Na + and Ca 2+ channels (Leaf et al, 2005)].…”
Section: Introductionmentioning
confidence: 99%